The lazy root : Will a change in the rainfall regime or increased anthropogenic nitrogen result in an alteration in the competitive balance between trees and grassed in a semi-arid South Africa savanna? - Bell, Wesley Drummond (Department of Biological Sciences, 2017)
In an attempt to determine why trees and grasses are able to coexist in savannas, Walter (1971) first proposed the root niche separation model for savannas which suggests that trees and grasses have differential access to water due to spatial differences in their rooting profiles. Subsequent studies in various savannas around the world have found that this is often not the case. In the central region of the Kruger National Park February & Higgins (2010) found that trees and grasses root at the same depths within the soil profile. In this study I determine whether the existence of fine roots in the soil profile necessarily indicates root activity. I also aim to determine the effect of increased water and nitrogen availability on root activity of trees and grasses. Pits of 20 x 20 em were dug to a depth of 40 em in plots that were either irrigated with the equivalent of 30 ml of rainfall per month or left without irrigation. This study was performed at the end of the rainfall season. I found that trees and grasses root at the same depths under moist and dry edaphic conditions as well as in plots with increased nitrogen. Tree roots are however, significantly more active than grass roots in non-irrigated plots. Temporal separation in root activity therefore seems to be a factor that allows for the coexistence of trees and grasses in savanna ecosystems.